PARTISIPASI MASYARAKAT MEMBANGUN JEMBATAN GANTUNG BERSAMA TIM PENGABDIAN MASYARAKAT POLITEKNIK NEGERI PADANG di DESA BUMI AYU, KECAMATAN SANGIR, SOLOK SELATAN - Yetri, Yuli; Hidayati, Rahmi; Maimuzar, Maimuzar; Hendra, Hendra; Nofriadi, Nofriadi (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
Community service has been completed by a community service team from the Politeknik Negeri Padang (PNP) in South Solok Regency. The purpose of this community service is to help the community in the construction of a suspension bridge in the village of Aai Manyuruak, Bumi Ayu Village, South Solok Regency. This community service can be carried out thanks to cooperation between the community and donors. The results of this dedication show that universities feel compelled to devote their knowledge to helping build suspension bridges that have been cut off, and have not been rebuilt due to lack of funds. The participation of donors and the community as well as the PNP community service team in the construction of the suspension bridge in Bumi Ayu village was entirely due to community activities carried out in mutual cooperation. Therefore, the construction of this suspension bridge is highly anticipated by the community in running the economy and access to education. In planning the construction of a suspension bridge, the community is fully involved, from planning to implementation. With the completion of the construction of this suspension bridge, the community and children going to school no longer need to take alternative roads which are quite far away.